2019
DOI: 10.7759/cureus.5126
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ice for Postoperative Total Knee Incisions – Does this Make Sense? A Pilot Evaluation of Blood Flow Using Fluorescence Angiography

Abstract: IntroductionTotal knee arthroplasty (TKA) is a common procedure with significant advances over the past several years, many pertaining to improved perioperative pain control. Cryotherapy is one method thought to decrease swelling and pain postoperatively. To our knowledge no study has directly visualized the effect cryotherapy has on skin blood flow following TKA. The primary aim was to determine if cryotherapy (icing) affects peri-incisional skin blood flow and if this is lessened with an alternate placement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Cryotherapy is a Non-pharmaceutical treatment to relief of postoperatively pain and swelling, which involves the application of cold to the skin surrounding the injured soft tissues and in joint surgery is supposed to reduce the temperature in knee-joint [7] . Low temperature will reduce local blood ow through vasoconstriction, which relieves the local in ammatory reaction, swelling and heat experience, and also will slow the conduction of nerve signals that potentially reducing pain transmission [10][11][12] . In addition, previous study has shown that a pleasant sensation evoked by knee icing also will reduce the pain intensity after TKA [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Cryotherapy is a Non-pharmaceutical treatment to relief of postoperatively pain and swelling, which involves the application of cold to the skin surrounding the injured soft tissues and in joint surgery is supposed to reduce the temperature in knee-joint [7] . Low temperature will reduce local blood ow through vasoconstriction, which relieves the local in ammatory reaction, swelling and heat experience, and also will slow the conduction of nerve signals that potentially reducing pain transmission [10][11][12] . In addition, previous study has shown that a pleasant sensation evoked by knee icing also will reduce the pain intensity after TKA [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Indocyanine green and near-infrared angiography have been used to assess perfusion of skin flaps, wound closures, abdominoplasties, and bowel anastomoses ( Diep et al, 2016 , Duggal et al, 2014 , Mirhaidari et al, 2018 , Pruimboom et al, 2020;4:CD013280. , Wyles et al, 2016 , Patel et al, 2013 , Moukarzel et al, 2020 , Wilke et al, 2021 , Rinker, 2016 , Foster et al, 2019 , Shannon et al, 2017 ). Given its success in similar applications, we sought to investigate the feasibility of using near-infrared angiography to evaluate skin perfusion before and after suture- or staple-assisted laparotomy closure during gynecologic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Indocyanine green (ICG) angiography provides the surgeon this ability and has successfully been used in plastic surgery, general surgery, and more recently in orthopaedic surgery, to predict the survival of tissue and planned flaps. [10][11][12][13] We recently reported on ICG angiography use in sarcoma surgery, demonstrating that it was predictive of developing a postoperative wound complication, especially in the lower extremity. 14 What is unknown, however, is whether use of this technology will translate to lower postoperative wound complication rates.…”
mentioning
confidence: 99%